2021
DOI: 10.1177/00187208211010004
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Regression Analysis of the Effects of Alert Presence and Scenario Criticality on Automated Vehicle Takeover Performance

Abstract: Objective This study investigates the impact of silent and alerted failures on driver performance across two levels of scenario criticality during automated vehicle transitions of control. Background Recent analyses of automated vehicle crashes show that many crashes occur after a transition of control or a silent automation failure. A substantial amount of research has been dedicated to investigating the impact of various factors on drivers’ responses, but silent failures and their interactions with scenario … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Perhaps the most relevant feature in relation to the findings of this study—in particular with regard to the minimum TTC—is the takeover time budget found in Du et al ( 5 ), which was identified as one of the important features in takeover performance prediction. Previous studies have shown that a shorter takeover time budget is associated with a shorter minimum TTC ( 11 ). Thus, our finding is aligned with the takeover time budget found in Du et al ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the most relevant feature in relation to the findings of this study—in particular with regard to the minimum TTC—is the takeover time budget found in Du et al ( 5 ), which was identified as one of the important features in takeover performance prediction. Previous studies have shown that a shorter takeover time budget is associated with a shorter minimum TTC ( 11 ). Thus, our finding is aligned with the takeover time budget found in Du et al ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The simulator’s automated driving system was activated with a button on a touch screen display located to the right of the steering wheel. When the system encountered a failure or an operational limit, the vehicle’s automated system was disabled (see Alambeigi and McDonald ( 11 ) for a detailed description).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These probability distributions can be used by system designers to select values to match their priorities and understand the uncertainty in their decisions. For example, if a TOR is designed to be issued 7 s prior to exiting the ODD, we cannot be sure that all drivers will manage to deactivate automation in that time, as the 95% HPD for the 95th percentile driver who is looking towards an NDRT item when the TOR is issued ranges between 5.1 s and 8.0 s. Despite the advantages of the Bayesian framework, it is rarely used in the literature on human factors of automated driving, with a few exceptions (e.g., [26], [27], [28]).…”
Section: B Association Between Ndrt Engagement or Repeated Exposure A...mentioning
confidence: 99%
“…SAE level 2 automated cars partially relieve individuals from the driving task. Silent failures in these automated vehicles lead to decreased engagement in monitoring the road, poorer take-over performance (Alambeigi et al, 2021;Louw et al, 2019;Mole et al, 2020) and delayed brake response times (Bianchi-Piccinini et al, 2020). Explicit failures, as opposed to silent ones, are notified to the users.…”
Section: Introductionmentioning
confidence: 99%